AN ERROR ANALYSIS OF DESCRIPTIVE ESSAY OF THE FOURTH SEMESTER STUDENTS OF ENGLISH DEPARTMENT PGRI UNIVERSITY OF BANYUWANGI - ABDUL HALIM; WAGEYONO WAGEYONO; YUNITA ERVIANA; ELOK FIKIANI (SOSIOEDUKASI, 2017)
Writing is an important skill in language learning. There are four components of the language skills are: listening, speaking, reading, and writing. Writing is a skill which can be learned by anyone who wants to express their thought, ideas, feeling, etc. To get the data of the research, the researcher used essay writing test as the instrument. The researchers used purposive sampling to take the sample that is a class 14A. Purposive of the research was taken from the Fourth Semester students of English Department PGRI University of Banyuwangi in the 2015/2016 academic year. They are 12 students as sample which was taken by using cluster random sampling. Based on data of the result and discussion, it can be concluded that type of errors made by the students in their English writing descriptive essay from the highest percentage to lowest are error of grammar, vocabulary and organization. The result of the error analysis process showed that the students committed error into three types, grammar, vocabulary, mechanics, content and organization. From the frequency of each error types, vocabulary was the error which most frequently produced by the students. makes error of mechanics 120 or 41,49% that capitalization is 61 or 21,32%. Punctuation is 59 or 20,62%.. With those frequency, the lecturer should pay more attention to this part. It indicates that the students are weak in making a precise set of a sentence in particular and in writing in genaral. The second level error, is vocabulary is 53 or 40,25 that are spelling is 14 or 4,89%. Addition word 23 or 8,04%. Word choice is 36 or 12,58%. Diction is 44 or 1,38%. %. The third level error, is grammar 21 or 16,41% that article is 14 or 4,89%. Singular or plural is 10 or 3,49%. Preposition is 8 or 2,79%. The fourth level error, is content 6 or ,09%. The last level error, is organization 11 or 3,84%.